Penegakan Hukum Terhadap Pelaku Kasus Femisida di Indonesia Studi Kasus: Pembunuhan di Cirebon - Fatikasari, Indi; Iim Imroatus Sholihah Hamid; Akhmad Khalimy; Dian Latifiani (Indonesian Journal of Criminal Law, 2024)
This study aims to examine the phenomenon of femicide in Indonesia, focusing on the murder case in Cirebon. Femicide, as a form of extreme violence against women, is often triggered by complex social, cultural, and economic factors. The research method used is descriptive qualitative with a sociological juridical approach, which includes news analysis and secondary data related to femicide cases. The results of the study indicate that the patriarchal structure that dominates society contributes to the high number of femicide, where many perpetrators are intimate partners of the victim. Law enforcement against perpetrators of femicide also faces significant challenges, including a lack of understanding of gender issues among law enforcement officers. This study recommends the need for more effective public policies and strict law enforcement to protect women and prevent future femicide.